The Kingfisher treasury of stories for seven year olds - "Edward" (London; Kingfisher Books, 1998)
A blend of familiar and unusual tales from all over the world. They include traditional stories, some by well-known authors, and others from overseas which have been re-told here by the co-compiler, Edward Blishen, editor of "The Junior Pears Encyclopedia" since 1963
Keywords: Short stories